Improving Student Learning Concentration in Chemistry Using the ‘Everyone Is a Teacher Here’ Strategy Assisted by Genially Media - Elferida Sormin; Nova Irawati Simatupang; Sumiyati Sumiyati; Dera Savera (Jurnal Penelitian Pendidikan IPA, 2025)
Student concentration in learning chemistry tends to be low due to the abstract nature of the material and the dominance of teacher-centered approaches. Innovative, student-centered strategies and interactive media are needed to enhance engagement and focus. This study aims to investigate the improvement of student learning concentration through the "Everyone Is a Teacher Here" (EIATH) strategy assisted by Genially media. A quasi-experimental design with one-group pretest-posttest was used, involving 36 students from class XI MIPA II at a Jakarta senior high school, selected through purposive sampling. Student concentration was measured using a validated non-test instrument based on a Likert scale. Data were analyzed using normality and homogeneity tests, followed by a paired sample t-test. The results showed that the data were normally distributed (p = 0.200) and homogeneous (p = 0.204). The paired t-test indicated a significant improvement in student concentration (t = 73.3 > t table = 1.68957). However, the N-Gain score was 0.2, indicating a low level of improvement. Discussion: Although the EIATH strategy, assisted by Genially media, significantly enhanced student concentration, the low N-Gain score suggests that its implementation needs to be further optimized. The combination of active learning and interactive media holds potential but may require extended application and supportive classroom conditions to achieve higher impact. The "Everyone Is a Teacher Here" strategy, supported by Genially media, has a positive effect on improving student learning concentration in chemistry, but refinement in implementation is necessary to achieve more substantial outcomes